ANALISIS PENGUKURAN TINGKAT KESEHATAN PERBANKAN SYARIAH DENGAN MENGGUNAKAN METODE CAMEL PADA PT. BANK MANDIRI SYARIAH Tbk. - Khristina Sri Prihatin; Siti Anjani (FKIP, Universitas Banten Jaya, 2021)
This study aims to determine the condition of the soundness of banks by way of assessment using the CAMEL method (Capital, Asset Quality, Management, Earning, and Liquidity). CAMEL analysis has five aspects, namely capital aspects using CAR (Capital Adequacy Ratio) ratio, asset quality aspects using KAP (Productive Asset Quality) ratio, management aspects using NPM (Net Profit Margin) ratio, profitability aspect uses ROA (Return on asset ratio) ) and BOPO (Operating Expenses to Operating Income), and Liquidity use the LDR (Loan to Deposit Ratio) ratio. This type of research was a type of quantitative research. Based on the characteristics of the problem raised by the researcher, this study was classified as a quantitative descriptive study. The data used in this study were secondary data obtained indirectly from Bank Syariah Mandiri. The data used were financial statement data (Financial Position Report and Income Statement) of PT. Bank Syariah Mandiri Tbk for three periods, namely 2016 to 2018. In addition, data were obtained from books, journals, internet or other media that support this research. Based on the results of research conducted at PT. Bank Syariah Mandiri Tbk shows that the value of the CAMEL in 2016 was 45.92 with the title NOT HEALTHY, in 2017 it was 45.92 with the NOT HEALTHY rating, and in 2018 was 47.68 with the NOT HEALTHY predicate.